Інститут літератури на сучасному етапі - Поліщук, О. (Слово і Час, 2018)
Стаття дає загальне уявлення про наукову роботу колективу Інституту літератури ім. Т. Г. Шевченка НАН України на сучасному етапі. До уваги читачів: коротка історична довідка про Інститут, інформація про основні завдання та актуальні напрями досліджень, структурні підрозділи установи, цінні зібрання рукописної спадщини – архівні фонди, а також бібліотечні фонди Інституту. У студії подано огляд основних результатів науково-дослідницької, видавничої діяльності (фундаментальні праці теоретико- та історико-літературного плану, проекти державного значення, індивідуальні та колективні монографії, видання літературно-художньої спадщини тощо), інформацію про організацію та проведення наукових, науково-популяризаційних заходів, експертну діяльність, роботу наукових рад, центрів, активну діяльність наукової молоді Інституту, міжнародну співпрацю установи, співпрацю із закладами вищої освіти, громадськими установами, масмедіа. У загальних рисах окреслено перспективні плани розвитку Інституту літератури, основні видавничі задуми, науково-дослідні проекти. The paper gives a general idea of the scholarly work carried out in Shevchenko Institute of Literature during the last years. It provides a brief historical reference, general information on the main tasks and actual directions of research, structural units of the institution, valuable collections of the manuscript heritage, archival and library funds of the Institute. The survey presents the main results of the research and publishing activities of the institution, points out the fundamental works in the fields of literary theory and history, both of individual and collective authorship, and names some significant academic editions of Ukrainian literary classics. In particular, it is emphasized that during the last decade several important projects of state importance were completed, “History of Ukrainian Culture” in 5 volumes (9 books) being among them. To the 200th anniversary of Taras Shevchenko’s birth, the Institute of Literature prepared and issued 6 volumes of “Shevchenko Encyclopedia”. The work on the other significant project, the 12-volume collection of works by Taras Shevchenko, has also been completed. The Institute also published volumes 1–4 of the academic “History of Ukrainian Literature” in 12 volumes. The first volume of the 7-volume “Franko Encyclopedia” appeared in print. Within the frame of regular work on the research themes, the staff of the Institute of Literature prepared and published a number of collective studies and collections of articles, namely: “Ukrainian Literary Criticism of the 20th Century: Anthology: in 2 vol.”, “Personal Library of Ivan Franko: Detailed Description: in 4 vol.” (vol. 1–2), “Taras Shevchenko and Imperial Censorship: Collection of Documents”, “Taras Shevchenko in Criticism”. The scholars of the Institute of Literature took part in the project of unique edition “Investigative and Supervisory Files on Taras Shevchenko (1847–1859)”. The institution also published three collections of the series “Theoretical Revisions”: “Modernism after Postmodern”, “Post-colonialism. Generation. Culture”, “Literature on the Field of Media” (Department of literary theory and comparative studies), “Existence of the Canon” (Department/Sector of slavic literatures), “Izbornyk 2012–2016” (Department of history of Ukrainian literature), “Ukrainian Literature of the 19th – Early 20th Century: Literary Word in the Nation’s Progress” (Department/sector of classical Ukrainian literature). The paper includes information on the research and educational events organized by the Institute; its expert activity; the work of scholarly councils and centers; international collaboration; cooperation with Universities, public institutions and mass media. The prospective plans for the development of the Institute of Literature, its major publishing plans and future research projects have been outlined as well.